2004
DOI: 10.1111/j.1469-7610.2004.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired disengagement of attention in young children with autism

Abstract: Our findings on disengagement in autism parallel those reported in normal 2-month-olds, in whom attention has been described as 'obligatory'. Discussion focuses on the potential role of general versus domain-specific processes in producing some of the core features of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
355
15
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 458 publications
(412 citation statements)
references
References 32 publications
31
355
15
8
Order By: Relevance
“…Study of scanpath progression found somewhat shorter scanpaths for the ASD participants, suggesting a tendency to explore areas closer to the current fixation than their TD peers. Investigation of fixation rate via a Poisson regression model indicated both the above differences were not simply due to a reduction in the rate of new fixations but rather fundamentally differing strategies adopted by each group, therefore we found no evidence of sticky attention, or delayed disengagement at the level of fixation, in our current dataset (Kikuchi et al 2011;Landry and Bryson 2004). Our data also reveal that interest in a more restricted area within scenes was not only found in the eye-tracking data but also in the verbal description data as participants with ASD missed significantly more areas within the scenes from their verbal descriptions than did the TD participants.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Study of scanpath progression found somewhat shorter scanpaths for the ASD participants, suggesting a tendency to explore areas closer to the current fixation than their TD peers. Investigation of fixation rate via a Poisson regression model indicated both the above differences were not simply due to a reduction in the rate of new fixations but rather fundamentally differing strategies adopted by each group, therefore we found no evidence of sticky attention, or delayed disengagement at the level of fixation, in our current dataset (Kikuchi et al 2011;Landry and Bryson 2004). Our data also reveal that interest in a more restricted area within scenes was not only found in the eye-tracking data but also in the verbal description data as participants with ASD missed significantly more areas within the scenes from their verbal descriptions than did the TD participants.…”
Section: Discussionmentioning
confidence: 57%
“…If found to be correct, our tailored models would enable us to establish whether differences were more likely a result of persistence within an area (South et al 2005;Pierce and Courchesne 2001) or reversion to previously explored areas (Pellicano et al 2011). Additionally, we were able to establish whether individuals with ASD generally moved their eyes over a shorter distance, as indicated by scanpath length, and whether there was a reduced fixation rate overall, which would support suggestions of individuals with ASD exhibiting delayed disengagement from the current fixation (Kikuchi et al 2011;Landry and Bryson 2004). We were also interested in the potential implications of more restricted viewing on perception and specifically whether verbal descriptions would also be more restricted.…”
Section: Individuals With Asd Generally Display Heightened Attention mentioning
confidence: 88%
“…Maybe attention disengagement is necessary for sharing attention on a more basic level, but once children use pointing behaviours, it may lose its importance. Important to note here is that joint attention on a lower level (alternates) rather than on a higher level (pointing) has been shown to be the more powerful discriminant marker of autism (e.g., Dawson et al, 2004) and that literature suggests that joint attention alternates may be sensitive to frontal lobe functional disturbance which may be central to fundamental features of autism (Landry & Bryson, 2004;Mundy, 2003;Schilbach et al, 2009). …”
Section: Attention Disengagementmentioning
confidence: 90%
“…To measure attentional skills, a visual orientation task was conducted, partially based on the paradigm of Landry and Bryson (2004). Stimuli were simple coloured line drawings, presented on a 21" LCD monitor.…”
Section: Tasks and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation